Giloy Ghanvati (Tinospora cordifolia (Willd.) Hook. f. and Thomson) Reversed SARS-CoV-2 Viral Spike-Protein Induced Disease Phenotype in the Xenotransplant Model of Humanized Zebrafish - Balkrishna, Acharya; Khandrika, Lakshmipathi; Varshney, Anurag (Frontiers in Pharmacology, 2021)
The current Severe Acute Respiratory Syndrome disease caused by Coronavirus-2 (SARS-CoV-2) has been a serious strain on the healthcare infrastructure mainly due to the lack of a reliable treatment option. Alternate therapies aimed at symptomatic relief are currently prescribed along with artificial ventilation to relieve distress. Traditional medicine in the form of Ayurveda has been used since ancient times as a holistic treatment option rather than targeted therapy. The practice of Ayurveda has several potent herbal alternatives for chronic cough, inflammation, and respiratory distress which are often seen in the SARS-CoV-2 infection. In this study we have used the aqueous extracts of Tinospora cordifolia (willd.) Hook.f. & Thomson in the form of Giloy Ghanvati, as a means of treatment to the SARS-CoV-2 spike-protein induced disease phenotype in a humanized zebrafish model. The introduction of spike-protein in the swim bladder transplanted with human lung epithelial cells (A549), caused an infiltration of pro-inflammatory immune cells such as granulocytes and macrophages into the swim bladder. There was also an increased systemic damage as exemplified by renal tissue damage and increased behavioral fever in the disease induction group. These features were reversed in the treatment group, fed with three different dosages of Giloy Ghanvati. The resultant changes in the disease phenotype were comparable to the group that were given the reference compound, Dexamethasone. These findings correlated well with various phyto-compounds detected in the Giloy Ghanvati and their reported roles in the viral disease phenotype amelioration.